Decreased COPD prevalence in Sweden after decades of decrease in smoking - Backman, Helena; Vanfleteren, Lowie; Lindberg, Anne; Ekerljung, Linda; Stridsman, Caroline; Axelsson, Malin; Nilsson, Ulf; Nwaru, Bright I.; Sawalha, Sami; Eriksson, Berne; Hedman, Linnea; Rådinger, Madeleine; et al. (Respiratory Research, 2020)
Background: COPD has increased in prevalence worldwide over several decades until the first decade after the millennium shift. Evidence from a few recent population studies indicate that the prevalence may be levelling or even decreasing in some areas in Europe. Since the 1970s, a substantial and ongoing decrease in smoking prevalence has been observed in several European countries including Sweden. The aim of the current study was to estimate the prevalence, characteristics and risk factors for COPD in the Swedish general population. A further aim was to estimate the prevalence trend of COPD in Northern Sweden from 1994 to 2009. Methods: Two large random population samples were invited to spirometry with bronchodilator testing and structured interviews in 2009–2012, one in south-western and one in northern Sweden, n = 1839 participants in total. The results from northern Sweden were compared to a study performed 15 years earlier in the same area and age-span. The diagnosis of COPD required both chronic airway obstruction (CAO) and the presence of respiratory symptoms, in line with the GOLD documents since 2017. CAO was defined as post-bronchodilator FEV 1 /FVC < 0.70, with sensitivity analyses based on the FEV 1 /FVC < lower limit of normal (LLN) criterion. Results: Based on the fixed ratio definition, the prevalence of COPD was 7.0% (men 8.3%; women 5.8%) in 2009–2012. The prevalence of moderate to severe (GOLD ≥ 2) COPD was 3.5%. The LLN based results were about 30% lower. Smoking, occupational exposures, and older age were risk factors for COPD, whereof smoking was the most dominating risk factor. In northern Sweden the prevalence of COPD, particularly moderate to severe COPD, decreased significantly from 1994 to 2009, and the decrease followed a decrease in smoking. Conclusions: The prevalence of COPD has decreased in Sweden, and the prevalence of moderate to severe COPD was particularly low. The decrease follows a major decrease in smoking prevalence over several decades, but smoking remained the ...